Exploring the relationship between cyberloafing and innovativeness among nurses in research hospitals: a cross-sectional study in Turkey - Semra Aciksoz; Merdiye Sendir; Nurdan Yalcin Atar; Nesibe Simsekoglu; Kursad Nuri Baydili (BMC, 2024)
Abstract Background Although cyberloafing, which refers to employees' use of the internet for private purposes outside of work, is seen as a negative behavior; Positive effects on areas such as individual development, learning opportunity, job satisfaction, productivity, change, organizational output, and innovation have also been reported. This study aims to investigate whether there is a significant relationship between cyberloafing and the innovativeness levels of nurses working in research hospitals in Turkey. Methods This analytical study consisted of 230 nurses. Data were collected using a nurse information form, Cyberloafing Scale, and Individual Innovativeness Scale. Data analysis was carried out using descriptive, comparative, and correlational statistics. Results Nurses had low levels of minor and severe cyberloafing scores and skeptical innovativeness. There was no correlation between cyberloafing and individual innovativeness. Conclusions More conscious cyberloafing should be encouraged through institutional arrangements, which can improve nurses' individual and innovative professional aspects.